Associated effects of lipopolysaccharide, oleic acid, and lung injury ventilator-induced in developing a model of moderate acute respiratory distress syndrome in New Zealand white rabbits - Tian, Xingyu; Lu, Bin; Huang, Yuyan; Zhong, Wenhao; Lei, Xin; Liu, Siyu; Tao, Tao; Yun, Fengning; Huang, Shiyong; Tan, Tiqing; Liu, Haifeng; Zhou, Ziyao; et al. (Frontiers in Veterinary Science, 2025)
Acute respiratory distress syndrome (ARDS) is a critical pulmonary disorder with manifestations of pulmonary edema, inflammation, and impaired oxygenation. Establishing reliable animal ARDS models has been critical for investigating its mechanisms and for testing pharmacological interventions. The present study sought to induce a moderate ARDS model in New Zealand White rabbits with a model involving a mix of lipopolysaccharide (LPS), oleic acid (OA), and ventilation-induced lung injury (VILI). Four experimental groups were established: negative control (NC, n = 4), OA (OM, n = 6), LPS + OA (LOM, n = 6), and LPS + OA + VILI (LOV, n = 6). Throughout the modeling process, vital signs (MAP and HR), respiratory parameters (Cdyn), and hematological indices (WBC and P/F) were continuously monitored, and lung ultrasound was performed. After the experiment, bronchoalveolar lavage fluid (BALF) was collected to measure total protein content, and lung tissue samples were collected to determine the wet-to-dry (W/D) ratio. HE-stained lung tissue sections were prepared and scored according to the ATS guidelines for lung injury scoring. The LOV group showed the most severe lung injury, significantly decreasing MAP and Cdyn. Pathological and ultrasound scores were considerably higher in the LOV group compared to the OM and LOM groups (p < 0.05). The lung W/D ratio was significantly higher in the LOM (6.68 ± 0.56) and LOV (7.40 ± 0.56) groups compared to the NC group (5.20 ± 0.16) (p < 0.05). At T6, the PaO2/FiO2 ratio in the LOV group was ≤200 mmHg, significantly lower than that in the NC group (p < 0.05). Some rabbits in the OM and LOM groups also had PaO2/FiO2 ratios ≤200 mmHg, but the difference compared to the NC group was not statistically significant. In conclusion, this study established a novel moderate ARDS model in New Zealand White rabbits using LPS, OA, and VILI. The model demonstrates severe lung damage, pulmonary edema, and sustained hypoxemia, providing a basis for future research.